A Resumable Fluorescent Probe BHN-Fe3O4@SiO2 Hybrid Nanostructure for Fe3+ and its Application in Bioimaging - Xi Zhou; Yujiao Wang; Qi Peng; Weisheng Liu (Nanoscale Research Letters, 2017)
Abstract A multifunctional fluorescent probe BHN-Fe3O4@SiO2 nanostructure for Fe3+ was designed and developed. It has a good selective response to Fe3+ with fluorescence quenching and can be recycled using an external magnetic field. With adding EDTA (2.5 × 10−5 M) to the consequent product Fe3+-BHN-Fe3O4@SiO2, Fe3+ can be removed from the complex, and its fluorescence probing ability recovers, which means that this constituted on-off type fluorescence probe could be reversed and reused. At the same time, the probe has been successfully applied for quantitatively detecting Fe3+ in a linear mode with a low limit of detection 1.25 × 10−8 M. Furthermore, the BHN-Fe3O4@SiO2 nanostructure probe is successfully used to detect Fe3+ in living HeLa cells, which shows its great potential in bioimaging detection.